Autologous Muscle-derived Cell Injection for Treatment of Female Stress Urinary Incontinence: A Single- Arm Clinical Trial with 24-months Follow-Up - Sharifiaghdas, Farzaneh; Zohrabi, Farshad; Moghadasali, Reza; Shekarchian, Soroosh; Jaroughi, Neda; Bolurieh, Tina; Baharvand, Hossein; Aghdami, Nasser (Urology Journal, 2019)
Purpose: This clinical study evaluated the effect of autologous muscle-derived cell (MDC) injection for the treatment of female patients with pure stress urinary incontinence (SUI). Materials and Methods: A total of 20 women with SUI received transurethral injections of autologous MDCs. Baseline and follow-up evaluations consisted of physical examinations (cough stress tests), one-hour pad test, Incontinence Impact Questionnaire-7 (IIQ-7), and Urogenital Distress Inventory (UDI-6) scoring. The patients were followed one week as well as 1, 3, 6, 9, 12, and 24 month(s) after the procedure. Multichannel urodynamic study were performed before and 24 months after the intervention. The incidence and severity of adverse events (AE) were also recorded at each follow-up visit. Results: A total of 20 eligible female patients with the chief complaint of SUI that was unresponsive to conservative management, was enrolled in the trial, 17 of whom completed all follow-up visits. At 12th months, 10 (59%) patients had complete response, whereas 2 (12%) and 5 (29%) patients had partial and no response, respectively. At 24th months, relapse of SUI in 5 out of 10 complete responders (29%) and 2 out of 2 partial responders to the treatment, respectively. The intervention produced no serious AE during the trial. Conclusion: According to our results, though obtained from a limited number of patients, MDC therapy was a minimally invasive and safe procedure for treatment of female patients with pure SUI. However, currently, the efficacy of this type of treatment for SUI is not sufficiently high and multi-center randomized clinical trials are required to be conducted before reaching a concrete conclusion.